Ultrasound assessment of tibial nerve cross-sectional area in diabetic peripheral neuropathy in the Thai Population - Athikhun Suwannakhan; Sittichai Khamsai; Thongchai Pratipanawatr; Woranan Kirisattayakul; Waranon Munkong; Nongnuch Prab Na Sak; Waritsara Phonsena; Sitthichai Iamsaard; Thanyaporn Senarai (PLoS ONE, 2026)
Early recognition of DPN gives physicians the opportunity to deliver appropriate treatment and counseling to minimize subsequent complications. This study aimed to evaluate the diagnostic performance of tibial nerve cross-sectional area (CSA) in detecting DPN using a Modified Toronto Clinical Neuropathy Score (mTCNS) ≥ 3 as the diagnostic reference in Thai diabetic patients. A total of 67 diabetic patients (120 limbs) were enrolled from Srinagarind Hospital between 2022 and 2023. A total of 120 limbs belonging to 67 patients were categorized into two groups: non-DPN group (mTCNS < 3) (n = 42) and DPN group (mTCNS ≥ 3) (n = 78). Tibial nerve CSA was measured 3 cm proximal to the medial malleolus using ultrasound. Clinical parameters and metabolic profiles were recorded. Receiver operating characteristic analysis, correlation analyses, and multivariable logistic regression were performed to evaluate diagnostic utility and associations between CSA and clinical parameters. The tibial nerve CSA was significantly higher in the DPN group (13.49 mm 2 , 95% CI: 12.84–14.13) compared to the non-DPN group (11.98 mm 2 , 95% CI: 10.95–13.02) (p = 0.015). A CSA threshold of 13 mm 2 yielded a sensitivity of 58.5% and specificity of 74.2%. CSA positively correlated with mTCNS (r = 0.49, p < 0.001) and sensation score (r = 0.37, p = 0.002) in DPN patients. Logistic regression identified CSA and estimated glomerular filtration rate as independent predictors of DPN status. Tibial nerve CSA may serve as a useful structural marker to support the identification of DPN. When used alongside established clinical assessments, CSA measurement could contribute to earlier detection and improved risk stratification in diabetic populations.